2013
DOI: 10.1002/admi.201300007
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Polymer Grafts: Synthesis and Characterization of Layered ‘Brush’ and ‘Gel’ Structures

Abstract: The development of surface coatings with well-defi ned architecture is of particular interest in several disciplines, notably in biomaterials. Bio-organic layers on different length-scales, featuring variable composition, structure and modulus have been observed in several biological systems, such as human cartilage, mammalian skin and the nacre of oyster shells. [1][2][3] These complex systems often consist of mechanically graded structures that resist and respond to external normal and shear forces, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…The lateral deformability of the POEGMA brushes and the frictional properties as a function of tethered chain length were subsequently measured by FFM. We recently demonstrated that friction loops of hydrated brushes show “tilted” profiles between scanning‐direction reversal and steady sliding . The tilted section of the loops originates from the lateral deformation of hydrated, surface‐tethered chains when they are subjected to a sliding probe under load.…”
Section: Resultsmentioning
confidence: 99%
“…The lateral deformability of the POEGMA brushes and the frictional properties as a function of tethered chain length were subsequently measured by FFM. We recently demonstrated that friction loops of hydrated brushes show “tilted” profiles between scanning‐direction reversal and steady sliding . The tilted section of the loops originates from the lateral deformation of hydrated, surface‐tethered chains when they are subjected to a sliding probe under load.…”
Section: Resultsmentioning
confidence: 99%
“…18 We also demonstrated that the growth of homopolymer brushes can be interrupted and reinitiated multiple times without any notable loss in polymerization efficiency, which is an essential prerequisite for the successful construction of block-copolymer brushes. A further condition for the growth of such brushes is successful chain-end reinitiation with a second monomer, rather than the formation of new chains from the unreacted initiators remaining on the substrate surface, as reported by Li et al 19 In the present study, we introduce a flow system coupled with a switching valve that can seamlessly switch the monomer solutions from one to another without interrupting the polymerization process. Previously, we have demonstrated that the dispersity of the tethered polymer chains in such reaction environment is fairly low which is possible only if there is no continuous reinitiation from unreacted initiators at the surface.…”
Section: Introductionmentioning
confidence: 85%
“…Then anotribological properties of PLL-g-X films were assessed by lateral force microscopy (LFM), recording friction force versus applied load profiles (FfL) on the different brush films. [38,39] As displayed in Figure 4, PEOXA brushes showed the highest friction among the different films studied, probably because of their limited hydration and amphiphilic character.I nc ontrast, an improvement in the lubrication properties was found for PMOXA, PMOZI, and PEG brushes,w ith the latter two brush types displaying the lowest friction.…”
Section: Angewandte Chemiementioning
confidence: 97%